Measured and predicted resting metabolic rate of Paralympic athletes - Weijer, V. C. R.; Jonvik, K. L.; Risvang, l.; van Dam, C. H. J.; Raastad, T.; van Loon, L. J. C.; van Dijk, J. W. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Resting metabolic rate (RMR) is an important determinant of daily energy expenditure. In Paralympic athletes, resting metabolism may be affected by a unique body composition, missing or inactive body parts, and neurological conditions. This study aimed to assess the RMR and its potential predictors in Paralympic athletes. Secondly, we evaluated the level of agreement between athletes` measured and predicted RMR.